Magnetic resonance elastography of malignant tumors - Pagé, Gwenaël; Garteiser, Philippe; Van Beers, Bernard E. (Frontiers in Physics, 2022)
Cancer biomechanical properties, including high stiffness, solid stress, and interstitial pressure, as well as altered micro-architecture, are drivers of tumorigenesis, invasiveness and resistance to treatment. Magnetic resonance elastography is an emergent non-invasive imaging method to assess the tumor mechanical properties in a spatially resolved fashion. Several MRE acquisition and reconstruction methods have been developed to assess tumors and surrounding tissues. It is increasingly recognized that the visco-elastic properties assessed with MRE are useful for characterizing malignant tumors and evaluating treatment response in various organs. Generally, malignant tumors, except brain tumors, have high stiffness and more particularly high visco-elastic ratio or fluidity. MRE transducers, acquisition sequences and reconstruction algorithms are continuously improved to increase depth penetration and spatial resolution, and limit artifacts at spatial discontinuities. Moreover, assessment of compression stiffening and of multifrequency stiffness dispersion may provide new biomarkers of the altered physical traits of cancer. Increasing research and clinical validation will improve the efficacy of MRE for cancer characterization.